Foundations of economic analysis - Samuelson, Paul A. (Cambridge : Harvard University Press, 1947)
The book sought to demonstrate a common mathematical structure underlying multiple branches of economics from two basic principles: maximizing behavior of agents (such as of utility by consumers and profits by firms) and stability of equilibrium as to economic systems (such as markets or economies). Among other contributions, it advanced the theory of index numbers and generalized welfare economics. It is especially known for definitively stating and formalizing qualitative and quantitative versions of the "comparative statics" method for calculating how a change in any parameter (say, a change in tax rates) affects an economic system. One of its key insights about comparative statics, called the correspondence principle, states that stability of equilibrium implies testable predictions about how the equilibrium changes when parameters are changed.
Includes bibliographical footnotes and index.
rpm 05/07/2017
Loans
Keywords: Economics, Mathematical